Determining the absolute efficiency of a delay line microchannel-plate detector using molecular dissociation - Gaire, B.; Sayler, A. M.; Wang, P. Q.; Johnson, Nora G.; Leonard, M.; Parke, E.; Carnes, K. D.; Ben-Itzhak, I. (My University, 2007)
We present a method to measure the absolute detection efficiency of a delay-line microchannel-plate detector using the breakup of diatomic molecular ions. This method provides the absolute total detection efficiency, as well as the individual efficiency for each signal of the detector. The method is based on the fact that molecular breakup always yields two hits on the detector, but due to finite detection efficiency some of these events are recorded as single particles while others are detected in pairs. We demonstrate the method by evaluating the detection efficiency for both timing and position signals of a delay-line detector using laser-induced dissociation of molecular ions. In addition, the detection efficiency as a function of position has been determined by dividing the detector into sectors.